Que Horas ela Volta? The Subordination of Domestic Employment and the Differential Distribution of Precariousness in Women's Lives - Dombkowitsch, Luciana Alves (2016)
This study questions the subordination of domestic employment and the differential distribution of precariousness in the lives of women, taking as its starting point the film QUE HORAS ELA VOLTA?  The filmic work reflects life narratives of Brazilian women who leave in search of their professional dreams, where domestic work, at the expense of their affections and desires. Used a qualitative approach with emphasis on cultural feminist studies. Thus, the research aims to advance the discussions on gender studies as urgent demands found in the bodies of women, whose invisibility and silence perpetuate historical and socially.